Omotic lexicon in its Afro-Asiatic setting VIII: Further addenda to the Omotic roots with *b- + dentals and sibilants (Part 1) - Takács, Gábor (Lingua Posnaniensis, 2021)
The paper constitutes part of a long-range series aiming, step by step, to identify the inherited Afro-Asiatic stock in the etymologically little explored lexicon of the Omotic (West Ethiopia) branch of the Afro-Asiatic family displaying the least of shared traits among the six branches of this macrofamily, which suggests a most ancient Omotic desintegration reaching far back to the age of post-Natufian neolithic.